Opportunistic Infections due to Candida auris in Patients with Multiple Comorbidities - Peetam Singh; Anita Pandey; Tanu Raj Sirohi (JK Science, 2025)
The Candida species are usually considered as commensals on skin, mucous membrane, and gastrointestinal tract. Among various non-albicans Candida species, Candida auris is gaining importance due to serious outbreaks of invasive infections in healthcare settings worldwide. We report a series of three clinical cases associated with Candida auris infections. All of these Candida auris isolates were identified by VITEK-2 compact automated system. The antifungal susceptibility data showed that all of the three Candida auris isolates were multi-drug resistant in nature and sensitive only to echinocandins including caspofungin and micafungin.